Dose-Dependent Effect of Statin Pretreatment on Preventing the Periprocedural Complications of Carotid Artery Stenting. Issue 7 (July 2017) - Hong, Jeong-Ho; Sohn, Sung-Il; Kwak, Jaehyuk; Yoo, Joonsang; Chang, Hyuk Won; Kwon, O-Ki; Jung, Cheolkyu; Chung, Inyoung; Bae, Hee-Joon; Lee, Ji Sung; Han, Moon-Ku
Abstract : Background and Purpose—: We investigated whether statin pretreatment can dose dependently reduce periprocedural complications in patients undergoing carotid artery stenting because of symptomatic carotid artery stenosis. Methods—: We enrolled a consecutive series of 397 symptomatic carotid artery stenosis (≥50% stenosis on conventional angiography) treated with carotid artery stenting at 2 tertiary university hospitals over a decade. Definition of periprocedural complications included any stroke, myocardial infarction, and death within 1 month after or during the procedure. Statin pretreatment was divided into 3 categories according to the atorvastatin equivalent dose: none (n=158; 39.8%), standard dose (<40 mg of atorvastatin, n=155; 39.0%), and high dose (≥40 mg; n=84; 21.2%). A multivariable logistic regression analysis with the generalized estimating equation method was used to investigate independent factors in periprocedural complications. Results—: The patients' mean age was 68.7 years (81.6% men). The periprocedural complication rates across the 3 categories of statin use were 12.0%, 4.5%, and 1.2%. After adjustment, a change in the atorvastatin dose category was associated with reduction in the odds of periprocedural complications for each change in dose category (standard-dose statin: odds ratio, 0.24; 95% confidence interval, 0.07−0.81; high-dose statin: odds ratio, 0.11; 95% confidence interval, 0.01−0.96; P for trend=0.01). Administration of antiplatelet drugs was also an independent factor in periprocedural complications (OR, 0.18; 95% CI, 0.05−0.69). Conclusions—: This study shows that statin pretreatment may reduce the incidence of periprocedural complications dose dependently in patients with symptomatic carotid artery stenting. Abstract : Supplemental Digital Content is available in the text.